WRITING ABOUT WHAT WE SEE: EKPHRASIS TODAY - Josie Arnold (University of Kuningan, 2016)
Visual media presents us with an opportunity to enter into the written scholarly discussions about an understanding of the paradox that what is seen and what is written are different representation. In this paper I investigate the importance of audience today; I discuss how global communications via new media challenges traditional views of the concept of an audience. I look at how communication is now from one to many, from many to many and from one to one, and how this challenges the term ‘audience’ with ‘users’. This paper enters into the scholarly debate about how interactivity in new media places singular interpretive actions by individuals at its center rather than as the more traditionally peripheral audience. In doing so it suggests that existing audience theory can and should be extended in regard to new media audiences, players or users. This paper also discusses how audience theory remains apposite when it adapts and changes.Keywords: visual media, audience, new media, audience theory